From Handmaiden of Theology to Handmaiden of Area Studies: Philological Approaches to Arabic-Islamic Studies in Norway - Eggen, Nora S. (Islam and Christian-Muslim relations, 2018)
This article presents the history of Arabic-Islamic studies in Norway, within the wider framework of Scandinavia and Europe. While Semitic studies reach well back into the sixteenth century in Sweden and Denmark, it was only in the early nineteenth century that the study of Arabic was introduced into Norway with the establishment of a university in 1811. From their inception, Arabic and Semitic studies were instrumental in reaching out into the world as well as in defining the national self-identity. I discuss these developments and the role and function philology played in various studies, programmes and disciplines, taking into account the shifting historical and sociocultural contexts. Issues of relevance and utility value as well as diverse political and economic concerns have throughout history formed the structural frameworks. Simultaneously, however, I demonstrate how individual motivation and impetus have continued to be of vital importance to the development of the fields. Finally, I discuss some of the current challenges and prospects for philological studies, and argue for the continued relevance for these methodological approaches.